The Effect Of Performance – Like Speed Endurance Exercises On The Development Of Forehand and Backhand Performance Accuracy In Squash Players - Staar, Hasnaa; Ismael, Hala (Journal of Physical Education, 2017)
The aim of the research is to identify the effect of speed endurance exercises on the development of backhand and forehand performance accuracy in squash players. The researchers used the experimental method. The subjects were (10) equally divided into two equal groups; experimental group and controlling group. Many tests were applied to measure the accuracy of forehand and backhand. The data was collected and treated using proper statistical operations. The researchers concluded that the proposed exercises developed the accuracy of forehand and backhand performance accuracy